Effectiveness of open and arthroscopic rotator cuff repair (UKUFF) - Carr, A; Cooper, C; Campbell, M; Rees, J; Moser, J; Beard, D; Fitzpatrick, R; Gray, A; Dawson, J; Murphy, J; Bruhn, H; Cooper, D; et al. (British Editorial Society of Bone and Joint Surgery, 2017)
Aims The appropriate management for patients with a degenerative tear of the rotator cuff remains controversial, but operative treatment, particularly arthroscopic surgery, is increasingly being used. Our aim in this paper was to compare the effectiveness of arthroscopic with open repair of the rotator cuff. Patients and Methods A total of 273 patients were recruited to a randomised comparison trial (136 to arthroscopic surgery and 137 to open surgery) from 19 teaching and general hospitals in the United Kingdom. The surgeons used their usual preferred method of repair. The Oxford Shoulder Score (OSS), two years post-operatively, was the primary outcome measure. Imaging of the shoulder was performed at one year after surgery. The trial is registered with Current Controlled Trials, ISRCTN97804283. Results The mean OSS improved from 26.3 (standard deviation (sd) 8.2) at baseline, to 41.7 (sd 7.9) two years post-operatively for arthroscopic surgery and from 25.0 (sd 8.0) to 41.5 (sd 7.9) for open surgery. Intention-to-treat (ITT) analysis showed no statistical difference between the groups at two years (difference in OSS score -0.76; 95% confidence interval (CI) -2.75 to 1.22; p = 0.452). The confidence interval excluded the pre-determined clinically important difference in the OSS of three points. The rate of re-tear was not significantly different between the two groups (46.4% for arthroscopic and 38.6% for open surgery; 95% CI -6.9 to 25.8; p = 0.256). Healed repairs had the most improved OSS. These findings were the same when analysed per-protocol. Conclusion There is no evidence of difference in effectiveness between open and arthroscopic repair of rotator cuff tears. The rate of re-tear is high in both groups, for all sizes of tear and ages and this adversely affects the outcome.